2007
DOI: 10.1007/s10126-007-9043-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycosporine-Like Amino Acids Extracted from Scallop (Patinopecten yessoensis) Ovaries: UV Protection and Growth Stimulation Activities on Human Cells

Abstract: Scallops (Patinopecten yessoensis) are extensively cultured and landed in Japan. During the processing of scallops, large amounts of internal organs and shells are discharged as industrial wastes. To reduce the burden on the environment, effective utilization and disposal methods of the wastes are required. Therefore, we have screened for useful materials in scallop internal organs, and found ultraviolet (UV) absorbing compounds from scallop ovaries. Based on UV absorption, electrospray ionization-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 33 publications
1
68
0
2
Order By: Relevance
“…These compounds were used as authentic standards [39] for the comparison of retention times on HPLC analysis. Hitachi L-4200 UV-VIS detector.…”
Section: Maa Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were used as authentic standards [39] for the comparison of retention times on HPLC analysis. Hitachi L-4200 UV-VIS detector.…”
Section: Maa Standardsmentioning
confidence: 99%
“…In the 13 C-NMR spectrum of the 464-Da MAA, the known chemical shifts for shinorine [39,47] were observed in the 464-Da MAA (Table S2). This finding suggests a shinorine scaffold in the 464-Da MAA.…”
Section: Variety Of Maas In Genotype Amentioning
confidence: 99%
“…There is evidence that presence of MAAs (such as shinorine, porphyra-334 and mycosporine-glycine) protect human fibroblast cells from UV irradiation and it was observed that all the three examined MAAs protect the cells from UV-induced cell death (Oyamada et al, 2008). However, mycosporine-glycine was found to be more effective.…”
Section: Discussionmentioning
confidence: 97%
“…Misonou et al (2003) studied the protective effects of MAAs against DNA damage and found that they were able to effectively block thymine dimer formation by UV radiation. Oyamada et al (2008) examined the protective effects of three different kinds of MAAs (shinorine, porphyra-334 and mycosporine-glycine) on human fibroblast cells and found that all three protected the cells from UV-induced cell death, with mycosporine-glycine having the strongest effect. They also found a promotional effect of MAAs on the proliferation of human skin fibroblast cells, and concluded that these secondary metabolites have potential application in cosmetics and toiletries.…”
Section: Mycosporine-like Amino Acids (Maas)mentioning
confidence: 99%